Obstetric near miss events and maternal deaths in a tertiary care hospital - Patil, Vrinda; Kamath, Vidya; Desai, Rathnamala M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal mortality is one of the important indicators of maternal health. Objectives of present study were to determine the frequency of maternal near miss, maternal near miss incidence ratio, maternal near miss to mortality ratio and mortality index and to study the risk factors associated with near miss events. Methods: A retrospective analysis of severe maternal morbidity from January 2015 to December 2015 was studied. Data was collected from women with pregnancy related life-threatening complications, near miss cases and maternal deaths. Results: The total number of deliveries were 5247. The numbers of maternal deaths were 12. Maternal mortality ratio was 228 per one lakh deliveries. There were 5.3 near miss events for every 1 maternal death. The nature and course of near miss cases were analysed. Severe maternal odds ratio was 14.48. Mortality index was 15.78%. Maternal near miss incidence ratio was 12.19. Conclusions: Near Miss Mortality indicator is helpful in identifying the life-threatening conditions and thus aiming to prevent maternal mortality. Hypertensive disorders and its complications are the leading causes of near miss events. Sepsis is the main cause of maternal death.